The origins of African American literature, 1680-1865 - Bruce, Dickson D., 1946- (Charlottesville : University Press of Virginia, 2001)
The Origins of African American Literature is an invaluable revelation of the emergence and sources of the specifically African American literary tradition and the forces that helped shape it.
Background to an African American literature, 1680-1760. -- The age of revolution, 1760-1800. -- Literary identity in the new nation, 1800-1816. -- The era of colonization, 1816-1828. -- The Liberator and the shaping of African American tradition, 1829-1832. -- Literary expression in the age of abolitionism, 1833-1849. -- African American voices in the American crisis, 1850-1861. -- The war for emancipation and beyond.
Includes bibliographical references (pages 335-360) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: American literature -- African American authors -- History and criticism; American literature -- Colonial period, ca. 1600-1775 -- History and criticism; American literature -- Revolutionary period, 1775-1783 -- History and criticism; American literature -- 19th century -- History and criticism; American literature -- 1783-1850 -- History and criticism; African Americans -- Intellectual life -- 17th century; African Americans -- Intellectual life -- 18th century; African Americans -- Intellectual life -- 19th century; Enslaved persons' writings, American -- History and criticism; African Americans in literature; Slavery in literature; African Americans -- Intellectual life; Littérature américaine -- Auteurs noirs américains -- Histoire et critique; Littérature américaine -- 1600-1775 (Période coloniale) -- Histoire et critique; Littérature américaine -- 1775-1783 (Période révolutionnaire) -- Histoire et critique; Littérature américaine -- 19e siècle -- Histoire et critique; Littérature américaine -- 1783-1850 -- Histoire et critique; Écrits d'esclaves américains -- Histoire et critique; Noirs américains -- Vie intellectuelle; Noirs américains dans la littérature.; Esclavage dans la littérature.; Littérature américaine -- ca 1600-1775 (Période coloniale) -- Histoire et critique; Noirs américains -- Vie intellectuelle -- 17e siècle.; Noirs américains -- Vie intellectuelle -- 18e siècle.; Noirs américains -- Vie intellectuelle -- 19e siècle.; LITERARY CRITICISM -- American -- General; LITERARY CRITICISM -- American -- African American; African Americans in literature; African Americans -- Intellectual life; American literature; American literature -- African American authors; American literature -- Colonial period; American literature -- Revolutionary period (United States); Slavery in literature; Enslaved persons' writings, American; 1600-1899; Criticism, interpretation, etc